2020
DOI: 10.1038/s41374-020-0455-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiclass cancer classification in fresh frozen and formalin-fixed paraffin-embedded tissue by DigiWest multiplex protein analysis

Abstract: Histomorphology and immunohistochemistry are the most common ways of cancer classification in routine cancer diagnostics, but often reach their limits in determining the organ origin in metastasis. These cancers of unknown primary, which are mostly adenocarcinomas or squamous cell carcinomas, therefore require more sophisticated methodologies of classification. Here, we report a multiplex protein profiling-based approach for the classification of fresh frozen and formalin-fixed paraffin-embedded (FFPE) cancer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Gene expression [36][37][38] and protein profiling [39][40][41] have been successfully applied to the classification of other tumor entities by tissue of origin. A recent study [17] showed the superiority of a DNA methylation-based classifier over both of these approaches in distinguishing HNSC metastases from primary lung carcinoma, suggesting that this method is more promising for the goal of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene expression [36][37][38] and protein profiling [39][40][41] have been successfully applied to the classification of other tumor entities by tissue of origin. A recent study [17] showed the superiority of a DNA methylation-based classifier over both of these approaches in distinguishing HNSC metastases from primary lung carcinoma, suggesting that this method is more promising for the goal of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, machine learning (ML) techniques have contributed to diagnosis in pathology [8–13]. Models based on DNA methylation profiles have been used to classify CNS tumors [14] and to predict the origin of neuroendocrine tumors [15] as well as CUPs [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown the potential of radiomics and ML-based classi ers for distinguishing metastases from primary lesions [27,28], suggesting that this method is promising for the goal of the present study. Although gene expression [22,29] and protein pro ling [30] have been successfully applied to the classi cation of other tumor entities by tissue of origin, they are preferably performed on freshfrozen samples as they are negatively affected by RNA and protein deterioration in formalin-xed, para n-embedded tissue [21]. Radiomics and ML-based methods can be applied more practically as MRI data are more readily available in routine diagnostic work.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most accurate techniques is the support vector machine (SVM) [5,6,7], which uses kernel functions to find a separating hyperplane in high-dimensional space. Other kernel methods include string kernels [8,9], which are widely used for DNA and RNA sequence data. However, SVM and related methods can be difficult to interpret.…”
Section: Introductionmentioning
confidence: 99%